Disordered Eating in Asian American Women: Sociocultural and Culture-Specific Predictors - Akoury, Liya M.; Warren, Cortney S.; Culbert, Kristen M. (Frontiers in Psychology, 2019)
Asian American women demonstrate higher rates of disordered eating than other women of color and comparable rates to European American women. Research suggests that leading sociocultural predictors, namely pressures for thinness and thin-ideal internalization, are predictive of disordered eating in Asian American women; however, no known studies have tested the intersection of sociocultural and culture-specific variables (e.g., ethnic identity, biculturalism, acculturative stress) to further elucidate disordered eating risk in this vulnerable, understudied group. Accordingly, this project used path analysis to simultaneously examine the role of sociocultural and culture-specific effects on disordered eating in Asian American college women (N = 430). Self-report measures assessing disordered eating, sociocultural (pressures for thinness; thin-ideal internalization) and culture-specific (ethnic identity, biculturalism, acculturative stress) variables revealed that a number of sociocultural and culture-specific factors are predictive of disordered eating. Consistent with prior research, heightened perceived pressures for thinness and thin-ideal internalization were predictive of disordered eating, and thin-ideal internalization partially mediated the relationship between pressures for thinness and disordered eating. Acculturative stress predicted disordered eating and fully accounted for the inverse relationship between biculturalism and disordered eating. Overall, findings highlighted the salience of sociocultural predictors for disordered eating in Asian American women and identified biculturalism and acculturative stress as culture-specific contributors that may uniquely impact vulnerability to disordered eating in Asian American women. Thus, the combined consideration of sociocultural and culture-specific factors may be important in disordered eating research and in the development of individualized treatment plans for Asian American women.